El debate sobre el uso de los espacios públicos, ¿andar por la calle desnudo o con la cara tapada? (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2015)
Must be allowed to walk naked or with the face hidden across the city? The limits of human rights: the protection of the rights of others.
Keywords: Nikab; protection of the rights of others; public nudity; public streets